1996
DOI: 10.1152/ajpregu.1996.271.6.r1500
|View full text |Cite
|
Sign up to set email alerts
|

Subthreshold stimulation of a serotonin 5-HT3 reflex attenuates cardiovascular reflexes

Abstract: Volume-sensitive and chemosensitive cardiopulmonary reflexes modulate volume homeostasis via renal sympathetic nerve activity (RSNA). Blunting of volume-sensitive cardiopulmonary reflexes is associated with volume retention, e.g., in hypertension, whereas the role of chemosensitive cardiopulmonary reflexes is largely unknown. To elucidate the possible role of chemosensitive cardiopulmonary reflexes in control of volume homeostasis, we investigated whether subthreshold stimulation of 5-HT3 receptors modulates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…First, they support the in vivo observation that the control of RSNA by mechanosensitive cardiopulmonary reflexes stimulated with a saline volume load was considerably impaired in rats preinfused with subthreshold doses of the serotonin 5-HT 3 receptor agonist PBG (30). In this respect, our findings allow for the hypothesis that serotonin 5-HT 3 receptors on cardiac afferent axons contained within the vagal nerve may directly influence the mechanosensitivity of these neural pathways.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…First, they support the in vivo observation that the control of RSNA by mechanosensitive cardiopulmonary reflexes stimulated with a saline volume load was considerably impaired in rats preinfused with subthreshold doses of the serotonin 5-HT 3 receptor agonist PBG (30). In this respect, our findings allow for the hypothesis that serotonin 5-HT 3 receptors on cardiac afferent axons contained within the vagal nerve may directly influence the mechanosensitivity of these neural pathways.…”
Section: Discussionsupporting
confidence: 84%
“…Our in vivo experiments (30) did not more precisely reveal in which way stimulated 5-HT 3 receptors (16) can interfere with the mechanosensitive properties of the afferent portion of the cardiorenal reflex. One mechanism could be that the stimulation of serotonin 5-HT 3 receptors on afferent cardiac fibers decreases mechanosensitivity.…”
mentioning
confidence: 76%
“…It was demonstrated that subthreshold stimulation of cardiopulmonary receptors by the 5-HT3 receptor agonist phenylbiguanide may attenuate cardiovascular reflexes. 26 The cardiovascular responses to stimulation of chemosensitive cardiac receptors were grossly preserved in diabetic rats. The interpretation of these results needs some considerations: (1) most ventricular afferents exhibit some degree of both mechanosensitivity and chemosensitivity.…”
Section: Protocol 1: Bezold-jarish Reflexmentioning
confidence: 99%
“…This effect was attributed to increased cardiac prostaglandin levels acting on cardiac afferent nerve fibers [65,66]. On the other hand, in normal rats the renal sympathoinhibitory response to a volume expansion with saline was severely blunted if accompanied by an infusion with a serotonin 5-HT 3 receptor agonist in a dose that itself could not elicit a cardiorenal reflex response [67]. Hence, in heart disease and hypertension, serotonin and other substances might further worsen the neurogenic control of renal sympathetic nerve activity, when afferent nerve fibers of the heart already respond with a decreased sensitivity to mechanical stimuli.…”
Section: Homeostatic Control Of Renal Sympathetic Nervesmentioning
confidence: 99%